2007
DOI: 10.1002/adsc.200700096
|View full text |Cite
|
Sign up to set email alerts
|

How does the Achiral Base Decide the Stereochemical Outcome in the Dynamic Kinetic Resolution of Sulfinyl Chlorides? A Computational Study

Abstract: Abstract:The dynamic kinetic resolution of sulfinyl chlorides by addition of the optically active alcohol DAGOH (diacetone d-glucose) in the presence of non-chiral bases was theoretically studied at the ONIOM (Becke3LYP:UFF) level. The dependence of the stereochemical outcome on the nature of the base observed in this reaction was explored considering two electronically similar bases, pyridine and collidine, that are experimentally known to promote opposite diastereoselectivities. Our calculations reproduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…In this regard, the "DAG-methodology" [54], developed in our group, seems the method of choice as it is able to give a diasteromerically pure sulfinate ester with a non-hindered alkyl chain at the sulfinyl sulfur. Additionally, based on our experimental and theoretical studies [55], both epimers at sulfur should be accessible in an enantiodivergent manner, by a simple change of the base used to catalyse the reaction, from the corresponding sulfinyl chlorides [56].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…In this regard, the "DAG-methodology" [54], developed in our group, seems the method of choice as it is able to give a diasteromerically pure sulfinate ester with a non-hindered alkyl chain at the sulfinyl sulfur. Additionally, based on our experimental and theoretical studies [55], both epimers at sulfur should be accessible in an enantiodivergent manner, by a simple change of the base used to catalyse the reaction, from the corresponding sulfinyl chlorides [56].…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Analysis of the optimized geometries revealed that the most sterically relevant substituent around the sulfur is the R group of the substrate when pyridine is used as the base, but it is the base itself when DIPEA (diisopropylethylamine) is used. This leads to an inversion of the chiral distribution of steric hindrance around the sulfur, and that in turn induces a reversal of the stereochemical outcome and results in the the observed enantiodivergence 28c…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the DAG sulfinate ester is thought to occur through the addition of the alcohol moiety of DAGOH to the sulfur centre of a sulfinyl chloride via an H-bonded trigonal bipyramidal transition state (Figure 2.7). [31] A tertiary amine base is thought to participate through the formation of an N-H bond with the hydrogen atom being transferred (Figure 2.7). The sulfinyl chloride is proposed to undergo pyramidal inversion in the presence of the tertiary base allowing for high reaction yields of diastereomerically enriched product from this racemic starting material.…”
Section: Synthesis Of Fluorine-tagged Chiral Sulfoxide Standardsmentioning
confidence: 99%
“…[26] ci When a less sterically active base, such as pyridine is used, the reaction proceeds to give the (R) sulfinate; when a bulkier base, such as diisopropylethyl amine or collidine is used, the pathway yielding the (5) sulfinate is preferred. [31] Steric interactions have been studied computationally for transition states of each of the four cases and the proposed rationalization for the observed diastereoselectivity is shown in Figure 2.8. [31] The upper half of the figure shows the most stable transitions states for the formation of the R-(left) and the 5-(right) diastereomers when pyridine is used.…”
Section: Synthesis Of Fluorine-tagged Chiral Sulfoxide Standardsmentioning
confidence: 99%
See 1 more Smart Citation